(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2021)
This essay relies on the historical figure of the camera obscura, as the site or place of articulation between the visible and the invisible. With the help of iconographic documents, it shows that it is not merely a process of inversion that defines the camera obscura. Indeed, a crucial spatial component is at play in the medium of the room itself: the camera is the very milieu where both an inversion and a displacement take place. From this perspective, it will appear more clearly that visibility does not stand beside or float above the invisible, but “takes place” right at its heart.